2008
DOI: 10.1253/circj.cj-08-0115
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Receptor Blockade Reduces Border Zone Myocardial Monocyte Chemoattractant Protein-1 Expression and Macrophage Infiltration in Post-Infarction Ventricular Remodeling

Abstract: eft ventricular (LV) remodeling after myocardial infarction (MI) is a process producing changes in LV geometry, such as progressive cavity dilatation, following infarct expansion, and it contributes to the development of heart failure (HF). 1 Inhibition of the cardiac renin -angiotensin system (RAS) prevents both LV remodeling and the transition from a compensatory state to decompensated HF after MI. [1][2][3][4] However, the precise mechanisms for the development of LV remodeling and the benefits of RAS inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
1
36
2
Order By: Relevance
“…23 Recent studies have shown that the marginal myocardial area might be a novel therapeutic target in the treatment of post-MI LV remodeling. 25,26 Extension of the macrophage-mediated inflammation in the infarcted region might cause the inflammatory response in the marginal region, although the mechanism underlying the inflammatory response in the latter has not been fully elucidated. In addition, geometric changes in hearts with LV aneurysm after MI are known to increase wall stress in the marginal region, 20 and pressure-overload-induced cardiac fibrosis is mediated through MCP-1 induction and macrophage accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Recent studies have shown that the marginal myocardial area might be a novel therapeutic target in the treatment of post-MI LV remodeling. 25,26 Extension of the macrophage-mediated inflammation in the infarcted region might cause the inflammatory response in the marginal region, although the mechanism underlying the inflammatory response in the latter has not been fully elucidated. In addition, geometric changes in hearts with LV aneurysm after MI are known to increase wall stress in the marginal region, 20 and pressure-overload-induced cardiac fibrosis is mediated through MCP-1 induction and macrophage accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The AT1 activation has a key role in these actions. The therapeutic use of ARB has extensively beneficial effects in attenuating the development of atherosclerosis and hypertension [29,[31][32][33]. Moreover, VSMCs play a fundamental role in maintaining vascular structure and function.…”
Section: Il-17mentioning
confidence: 99%
“…28 decreased, 13 suggesting involvement of sympathetic activation in the induction of inflammation. It has been also demonstrated that when an angiotensin II receptor antagonist was administered in a rat MI model, both expression of MCP-1 and macrophage infiltration in the border zone were reduced, 14 indicating the involvement of activation of the renin-angiotensin (RA) system in the promotion of inflammatory response. In chronic kidney disease patients with estimated glomerular filtration rate <60 ml · min -1 · 1.73 m -2 on admission 15 and those with the complication of so-called acute kidney injury (AKI) whose serum creatinine level increases to >0.3 mg/dl within 48 h of admission, 16 it is reported that peak CRP level increased concurrently with plasma interleukin (IL)-6 and serum malondialdehyde-modified low density lipoprotein (oxidized LDL) levels.…”
Section: Modification Of Crp Elevation By Patient Demographic Factorsmentioning
confidence: 99%